Effect of nanocrystalline cellulose on mechanical, thermal, and barrier properties of polylactic acid blown composite film. (9th February 2023) - Yu, Jie; Zhang, Feifei; Mu, Guangqing; Xu, Yunpeng; Qu, Junming; Zhang, Guixia; Lv, Yanna; Jiang, Shujuan; Qian, Fang; Xia, Ying
Abstract: This study utilized polyethylene glycol (PEG) as a compatibilizer, and prepared nanocrystalline cellulose (NCC) reinforced polylactic acid (PLA) nanocomposite films by blown film extrusion. The physical properties, including the mechanical performance, barrier characteristics, processing flow properties, and thermal properties, were evaluated, and the microstructure was estimated. The consequences showed that the NCC could significantly enhance the physical properties of the PLA nanocomposite film. When the NCC concentration was 3%, the tensile strength of the composite film was 45.02 MPa, and the melting index was 1.03 g/min, which were 17.85% and 6.40% greater than those of the PLA/PEG composite film, respectively. The oxygen transmission rate (OTR) of the composite film with NCC was 5.438 × 10 −4  cm 3 /(m 2 ·d·Pa), which was 96.70% lower compared to the composite film without NCC. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analysis showed that adding NCC and PEG could increase the stability of the PLA/PEG/NCC composite film, but NCC had little impact on the thermal properties of the PLA/PEG/NCC composite film. Scanning electron microscopy (SEM) analysis showed that the PLA, PEG and NCC had better compatibility and dispersion.